2021
DOI: 10.2196/29368
|View full text |Cite
|
Sign up to set email alerts
|

Understanding People’s Use of and Perspectives on Mood-Tracking Apps: Interview Study

Abstract: Background Supporting mental health and wellness is of increasing interest due to a growing recognition of the prevalence and burden of mental health issues. Mood is a central aspect of mental health, and several technologies, especially mobile apps, have helped people track and understand it. However, despite formative work on and dissemination of mood-tracking apps, it is not well understood how mood-tracking apps used in real-world contexts might benefit people and what people hope to gain from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 92 publications
3
26
0
Order By: Relevance
“…Additionally, tracking has been identified as a facilitator to user engagement in digital mental health intervention apps ( 45 ). Tracking can promote self-reflection ( 79 ), which was also observed in the current study. The results of the thematic analysis conducted in the current study revealed an overlap between the themes of additional features and performance.…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, tracking has been identified as a facilitator to user engagement in digital mental health intervention apps ( 45 ). Tracking can promote self-reflection ( 79 ), which was also observed in the current study. The results of the thematic analysis conducted in the current study revealed an overlap between the themes of additional features and performance.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, apps should personalize an experience with data collected through the app. Research shows that personalizing app content is critical for improving engagement with mental health apps ( 27 , 32 , 35 , 41 , 80 ). We should consider ways to personalize an experience in different stages of a user journey.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, research has mainly focused on analyzing user reviews to understand users’ opinions of mental health apps. Several efforts have been made for specific mental health disorders such as depression ( 23 ), bipolar disorder ( 24 ), and sleep disturbance ( 25 ), for specific types of app such as mood tracking ( 26 , 27 ), or for specific types of psychological treatments such as cognitive behavioral therapy (CBT) ( 28 ) and mindfulness ( 29 ). Other studies have focused on gaining an understanding of specific target group users, such as exploring adolescents’ perspectives on mental health apps ( 30 ), and mood-tracking apps considered useful to young people ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Participants will track and graph these weekly scores in a therapy notebook that is provided to them by the research team. Recent work analyzing mood-tracking within applications has found that apps with mood-tracking functionalities increase user self-awareness and understanding of emotions, making it an effective active therapeutic component [ 51 ].…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%